Treatment strategies and cumulative live birth rates in WHO-II ovulation disorders. (June 2018) - Braam, Sanne C.; de Bruin, Jan Peter; Buisman, Erato T.I.A.; Brandes, Monique; Nelen, Willianne L.D.M.; Smeenk, Jesper M.J.; van der Steeg, Jan Willem; Mol, Ben Willem J.; Hamilton, Carl J.C.M.
Abstract: Objective: To assess the live birth rate in women with WHO II anovulation and the proportion of women that need second or third line treatments if the initial therapy fails. Study design: In this multicenter cohort study we included couples with unfulfilled child wish who were referred to three fertility clinics in the Netherlands and selected women with a WHO II ovulation disorder as the only final infertility diagnosis (n = 468). Results: The cumulative live birth rate of the total group was 82% (383/468). The majority started with clomiphene-citrate as first-line treatment (n = 378) resulting in 180 (48%) live births. There were 153 couples (40%) who underwent a second-line treatment (recombinant-FSH or laparoscopic electrocoagulation of the ovaries, LEO) and 52 couples (14%) a third-line treatment (IVF/ICSI), resulting in 44% and 63% treatment dependent live births rates, respectively. Of all couples, 92 (20%) conceived naturally, 186 (40%) after clomiphene-citrate, 60 (13%) after recombinant-FSH, nine (2%) after LEO and 36 (8%) after IVF. Conclusion: Subfertile women with a WHO II ovulation disorder have a good prognosis on live birth, and most did so after ovulation induction with clomiphene-citrate. If first-line ovulation induction has failed ovulation induction with gonadotrophins or IVF still result in a live birth in about half of the cases.